AR-induced ZEB1-AS1 represents poor prognosis in cholangiocarcinoma and facilitates tumor stemness, proliferation and invasion through mediating miR-133b/HOXB8 - Jiang, Xingming (Aging (Albany NY), 2020)
Zinc finger E-box binding homeobox 1 antisense 1 (ZEB1-AS1) has displayed vital regulatory function in various tumors. However, the biological function of ZEB1-AS1 in cholangiocarcinoma (CCA) remains unclear. In this study, we confirmed that ZEB1-AS1 expression was increased in CCA tissues and cells, respectively. Upregulated ZEB1-AS1 was related to lymph node invasion, advanced TNM stage and poor survival of CCA patients. ZEB1-AS1 exhibited high sensitivity and specificity to be an independent poor prognostic factor of patients with CCA. Functionally, knocking down ZEB1-AS1 attenuated tumor cell stemness, restrained cellular viability in vitro and in vivo, and inhibited CCA cell migration and invasion by reversing epithelial-mesenchymal transition. For the mechanism, androgen receptor (AR) directly promoted ZEB1-AS1 expression, and further ZEB1-AS1 increased oncogene homeobox B8 (HOXB8) by sponging miR-133b. In addition, malignant phenotypes of CCA promoted by ZEB1-AS1 dysregulation were rescued separately through interfering miR-133b and HOXB8, suggesting AR/ZEB1-AS1/miR-133b/HOXB8 exerted crucial functions in tumorigenesis and progression of CCA.